Application of Risk Management in Rice Milling Business in Karangwuluh Village - Nida Aufa Al 'Asya; Amirah (JURNAL MANAJEMEN RISIKO, 2025)
This study aims to analyze the implementation of risk management in rice milling businesses in Karangwuluh Village. The research focuses on three main aspects: risk identification, risk evaluation and measurement, and risk management. A quantitative descriptive method was employed using descriptive statistical analysis based on questionnaire data from four active rice mill owners. The findings reveal that the overall implementation of risk management is categorized as high to very high. The average score for risk identification (4.50) and risk evaluation and measurement (4.475) indicates that business owners have strong capabilities in recognizing and assessing potential risks. The average score for risk management (4.00) demonstrates that respondents have applied mitigation strategies such as regular machine maintenance, supplier diversification, and post-incident evaluation. However, aspects related to risk documentation and financial management need improvement, particularly in establishing reserve funds and utilizing business insurance. The results of this study are expected to enhance the awareness and capability of rice mill entrepreneurs in managing risks effectively and contribute to the academic development of risk management in rural agricultural sectors.